Psychology and Contemporary Mental Health: A Conceptual Framework Of Fitrah, Nafs, Qalb, And 'Aql For Human Well Being: Psikologi dan Kesehatan Mental Kontemporer: Sebuah Kerangka Konseptual Fitrah, Nafs, Qalb, dan 'Aql untuk Kesejahteraan Manusia - Wiwied Widiyanti (Program Studi Psikologi Islam, 2026)
Purpose –This study aims to develop an integrative conceptual framework grounded in Islamic Psychology by incorporating the concepts of fitrah, nafs, qalb, and ‘aql to address contemporary mental health challenges. The paper argues that mental health can be understood as a process of realignment with humanity’s innate disposition (fitrah, nafs, ‘aql, and qalb), rather than merely the absence of psychopathology. Design/methods/approach – This study employs a qualitative conceptual approach through critical literature analysis and theoretical synthesis. Classical Islamic psychological sources and contemporary mental health literature were systematically reviewed and analytically mapped to construct an integrative framework linking Islamic anthropological constructs with modern psychological dimensions of cognition, emotion, behavior, and well-being Findings – The study finds that positioning fitrah as the ontological foundation of human psychology enables a holistic model in which psychological well-being emerges from the harmonious interaction of fitrah, nafs, qalb, and ‘aql. Mental and behavioral disorders are conceptualized as multidimensional disruptions involving spiritual misalignment, dysregulated desire, emotional imbalance, and impaired moral cognition. Research implications/limitations – As a conceptual study, the findings are limited by the absence of empirical validation. The framework requires further testing through quantitative, qualitative, or mixed-methods research to assess its applicability across clinical and cultural contexts. Originality/value – This study offers an original contribution by integrating fitrah into Islamic Psychology as a foundational construct for mental health, providing a spiritually grounded and culturally responsive model that enriches global mental health discourse and opens new avenues for interdisciplinary research